Skill wars : - Gordon, Edward E. (Butterworth Heinemann, 2000)
Skill Wars defines the race between advanced technology investment and human resources investment and shows managers how to measure that investment. It introduces a Human Capital Scoreboard of seven new business management/measurement tools including a more accurate calculation of ROI (Return on Investment) for employee performance improvement programs. It also provides case studies of how quality training can deliver on more problem-solving/thinking skills. It has a foreword by Joseph Boyett, author of The Guru Guide and Workplace 2000.